P Penerapan Model Pembelajaran Kooperatif Number Head Together untuk Peningkatan Pengetahuan Litrasi Sains Siswa pada Materi Metabolisme - Fransiska Radjak; Frida Maryati Yusuf; Aryati Abdul (Postgraduate, University of Mataram, 2023)
This research was conducted in class XII IPA 1 SMA N 1 Suwawa with the aim of knowing the literacy knowledge of students through the application of the Numbered Head Together cooperative learning model. The model used in this research is the Classroom Action Research Kemmis and Tagart models using 3 cycles, with research stages namely a) Planning, b) Implementation or action, c) Observation, d) Reflection. Based on the analytical instruments and analysis of scientific literacy-based learning outcomes, it can be seen that the NHT type cooperative learning model can increase students' scientific literacy knowledge which includes 3 indicators including scientific question assistance, explaining phenomena scientifically, and using scientific evidence , this is evidenced by improvements in the activities of teachers and students, as well as the improvement of learning outcomes achieved. The application of the NHT learning model can increase students' scientific literacy knowledge, because the application of the NHT learning model can help train and increase students' scientific literacy knowledge, especially in metabolic materials. The characteristics of metabolic substances which generally require more understanding can be complemented by the application of the NHT learning model which precipitates cooperation and sharing between peers which also requires responsibility for oneself due to random calling of noor. The advantages of the NHT learning model are that it can improve student achievement, are able to deepen student understanding, train student responsibility, delight students in learning, develop student curiosity and increase self-confidence also help increase students' scientific literacy knowledge because it involves students with their learning environment, and thinking activities together